Living the dream : putting your creativity to work (and getting paid) - Hiebert, Corwin (New Riders, 2013)
Living the Dream is a business book for creative people. It provides the insights and action steps they need to confidently put their skills and passions to work, to make the best business decisions possible, all in service of the ultimate goal--to make a living doing what they love. This inter-disciplinary, no-holds barred guidebook is for emerging and established creative small business owners. It delivers management, marketing ideas, and principles that can make independent creative work stress free and financially rewarding. Living the Dream is void of useless references to big companies, celebrity CEOs, or industry inbreeding. Instead, it gives creative people the real goods on proven business-building strategies without all the mumbo jumbo. This powerhouse of a book is focused on how to be successful and creative as a freelancer or small business owner. Through interviews, case studies, and features, the industry pros and subject matter experts provide the wisdom, objectivity, and context that creatives need. It's all about being creative and getting paid.